2016
DOI: 10.1016/j.pharep.2016.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Animal models of insulin resistance: A review

Abstract: Insulin resistance can be seen as a molecular and genetic mystery, with a role in the pathophysiology of type 2 diabetes mellitus. It is a basis for a number of chronic diseases like hypertension, dyslipidemia, glucose intolerance, coronary heart disease, cerebral vascular disease along with T2DM, thus the key is to cure and prevent insulin resistance. Critical perspicacity into the etiology of insulin resistance have been gained by the use of animal models where insulin action has been modulated by various tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(76 citation statements)
references
References 107 publications
1
67
0
8
Order By: Relevance
“…Animal models of T2D provide a useful tool to study this disorder, although they do not completely mimic the clinical aspects since they are all genetic models, both spontaneous and induced, in different species (to review see ref. ). Furthermore, a lack of information in some metabolic pathways or even contradictory effects described in different models implicate in a careful analysis of T2D.…”
Section: Dm and Disrupted Metal Balancementioning
confidence: 97%
“…Animal models of T2D provide a useful tool to study this disorder, although they do not completely mimic the clinical aspects since they are all genetic models, both spontaneous and induced, in different species (to review see ref. ). Furthermore, a lack of information in some metabolic pathways or even contradictory effects described in different models implicate in a careful analysis of T2D.…”
Section: Dm and Disrupted Metal Balancementioning
confidence: 97%
“…A significant positive correlation was detected between the saturated fatty acid and serum total cholesterol levels . Insufficient insulin secretion leads to blood lipid metabolism abnormalities and an increase in the CHO, and blood TG and LDL levels, which eventually cause a series of complications, such as cardiovascular disease and atherosclerosis . The data from this study indicated that a glycolipid metabolism disorder occurred in three monkeys.…”
Section: Discussionmentioning
confidence: 58%
“…На сьогодні методика оцінки вмісту інсуліну плазми крові міс-тить певні недоліки, оскільки для вивчення рівня базальної гіперінсулінемії відсутні загальноприйня-ті нормативні та порогові значення при поєднаному перебігу АГ та ЦД типу 2, а самі тести визначення базального інсуліну мають досить низьку відтворю-ваність [2,8].…”
Section: вступunclassified